MELKERSSON-ROSENTHAL SYNDROME-A RARE FINDING - Bajpai, Manas; Pardhe, Nilesh (Journal of Ayub Medical College Abbottabad, 2016)
A 43 year old male presented with the chief complaint of non-painful swelling of upper and lower lips from past one year. At anamnesis, we did not find any allergic disease, trauma and/or past recent injuries. Personal history revealed a facial palsy at the age of ten years as s singular manifestation. The physical examination revealed a painful, swollen upper and lower lip with bleeding and cracking on the surface (Figure-1) and scrotal tongue (Figure-2). Presence of all three manifestation from the past until present, prompted us to perform a biopsy from lip. Histological examination revealed several non caseating granulomas made up of lymphocytes centrally and large epithelloid cells at periphery,many multinucleated giant cells some of them are langerhans type dispersed in the connective tissue stroma, Areas of lymphoid follicle with germinal center were also seen (Figure-3). With the correlation of all the findings, a final diagnosis of monostotic Malkersson - Rosenthal syndrome was made. Melkersson - Rossenthal syndrome (MRS) is a very rare clinical entity. Its classical form is characterized by following triad: Facial nerve palsy, chelitis granulomatosa and fissured tongue.1 The presence of two or one manifestation mentioned above with chelitis granulomatosa in biopsy, is sufficient to diagnose monostotic MRS.2 Patients with a moderate form of granulomatous cheilitis show more benefit from the administration of steroids. Surgery is reserved for patients whose cheilitis does not respond to steroid therapy or who present a reasonable face deformation.3